Control of mRNA degradation in trypanosomes. (21st May 2008) - Clayton, Christine; Schwede, Angela; Stewart, Mhairi; Robles, Ana; Benz, Corinna; Po, June; Wurst, Martin; Quieroz, Rafael; Archer, Stuart
Abstract : Control of gene expression in trypanosomes relies almost exclusively on post-transcriptional mechanisms. Trypanosomes have the normal enzymes for mRNA decay: both the exosome and a 5′–3′-exoribonuclease are important in the degradation of very unstable transcripts, whereas the CAF1/NOT complex plays a major role in the degradation of all mRNAs tested. Targeted RNA interference screening was used to identify RNA-binding proteins that regulate mRNA degradation, and it revealed roles for proteins with RNA recognition motifs or pumilio domains.